Benchmarking analysis of digital light processing resins in terms of dimensional accuracy and geometric tolerances. (2022) - Stiuso, Vito; Minetola, Paolo; Giubilini, Alberto; Fontana, Luca; Singh Khandpur, Mankirat; Rifuggiato, Serena; Marchiandi, Giovanni
Abstract: Additive Manufacturing (AM) is a groundbreaking fabrication technology that is revolutionizing traditional manufacturing processes. Generally, following a layer-by-layer approach, in AM the final shape of the product is built through the progressive deposition of one or more materials. The most common extrusion-based AM technique for thermoplastic polymers is Fused Filament Fabrication (FFF), whilst for photopolymer resins, Digital Light Processing (DLP) and Stereolithography (SLA) are widely used. In the last years, DLP has spread rapidly, due to its low average cost and simple use. Moreover, a lower layer thickness can be used in DLP if compared to the FFF process. Therefore, hobbyists or amateur end users and many companies use DLP to achieve high dimensional accuracy and smooth surfaces for small products. This work aims to evaluate the performance of three different DLP resins in terms of dimensional and geometrical accuracy. A benchmarking activity is carried out using a Rover printer by Sharebot to produce replicas of a reference part using Sharebot resins. After production, the replicas were inspected using a Coordinate Measuring Machine (CMM) for comparing the dimensional accuracy of the geometric features according to ISO IT grades and tolerances of the GD&T system. The results of this study are also compared with previous works from the literature in the conclusions.